Comparative cost-effectiveness of tildrakizumab and other commonly used treatments for moderate-to-severe psoriasis. (3rd October 2021) - Wu, Jashin J.; Jia, Xiaoying; Zhao, Yang; Carrico, Justin; Brodtkorb, Thor-Henrik; Mendelsohn, Alan; Lowry, Simon; Feldman, Steven R.; Armstrong, April
Abstract: Objectives: To compare the cost-effectiveness of tildrakizumab with other commonly used biologics and apremilast as the first-line treatment for moderate-to-severe plaque psoriasis from a US health plan's perspective. Methods: A 10-year cost-effectiveness model was developed to compare the incremental cost per extra month with a Psoriasis Area and Severity Index (PASI) 75 response. Patients were assumed to receive one of the treatments evaluated as their first-line treatment at the outset of the analysis. Nonresponders (PASI <75) discontinued their current treatment; 25% went on to receive a mix of topical therapies, phototherapies, and other systemic therapies, while 75% received a second-line therapy before receiving a mix of topical therapies, phototherapies, and other systemic therapies. Direct medical costs were calculated based on drug acquisition, administration, and monitoring costs. Results: The incremental cost per extra month a patient had a PASI 75 response was lowest for brodalumab (3, 685), infliximab (4, 102), apremilast (4, 770), and tildrakizumab (5, 150), followed by risankizumab (5, 319), secukinumab (5, 675), guselkumab (5, 784), ixekizumab (5, 900), adalimumab (5, 943), ustekinumab (6, 131), etanercept (6, 618), and certolizumab pegol (13, 476). Conclusion: Tildrakizumab was among the most cost-effective first-line treatments for moderate-to-severe psoriasis and was more cost-effective than risankizumab, secukinumab, guselkumab, ixekizumab, adalimumab, ustekinumab, etanercept, and certolizumab pegol.